PERKIRAAN ULANG CADANGAN MUNGKIN PANAS BUMI TEMPERATUR MENENGAH DI INDONESIA: MEDIUM TEMPERATURE GEOTHERMAL POSSIBLE RESERVE REASSESSMENT IN INDONESIA - Husin Nugraha; Rina Wahyuningsih; Tony Rahadinata (Buletin Sumber Daya Geologi, 2022)
Accurate information about the value and characteristics of geothermal energy resources and reserves is needed in planning appropriate energy policies to optimize the utilization of geothermal resources in Indonesia. In addition, differences in the results of calculating geothermal energy resources and/or reserves by developers and the government cause the economic calculations of geothermal development projects in particular prospect area to also be different. This study performs a recalculation of geothermal medium temperature resources category by replacing the assumptions of several parameters with the assumptions of best practice parameters used in several literatures. The five parameters are thermal calculations contained in the fluid, final reservoir temperature, water saturation, electricity conversion factor and generating capacity factor. The results of this recalculation resulted in a geothermal resource value that was different from the results of the Geological Agency's calculations. The percentage difference between the calculations of the Geological Agency and this study indicates a strong correlation with reservoir temperature as shown by the R2 value of 85%. This strong correlation indicates that there is a systematic difference, which is suspected because in the Geology Agency's calculations it is assumed that there is a change in the water phase from the liquid phase to the vapor phase. The results of recalculation using the correlation equation with the reservoir temperature as an input resulted in the value of geothermal resources reduction by 27% or 940 MWe from the results of the Geological Agency's calculations. The recalculation result of medium temperature geothermal resources which previously reached 3,482 MWe reduced to a total of 2,541 MWe.